Some Observations on Troop Structure, Activity Budget and Food Habits of the Nilgiri Langur (Presbytis johnii) in Periyar During Monsoon (June - August) - Srivastava, K. K.; Zacharias, V. J.; Bhardwaj, A. K.; Joseph, Petrisia; Joseph, Sherly (Indian Forester, 1996)
To compare the troop and territory sizes, food habits and activity budgets of Nilgiri Langur in Periyar Tiger Reserves in monsoon seasons, a study was conducted and results are summarized.